The Use of Indonesian-English Code Mixing in One of Molita Lin’s YouTube Video as Beauty Vlogger - Auliabella, Putu Prahasti Des (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
The occurrence of code mixing phenomenon was unavoidable, moreover in the bilingual society such as Indonesia, where the speakers communicate by in other (foreign) languages besides their national or local languages. There is no exception to Molita Lin, an Indonesian beauty vlogger who produces and uploads videos about beauty-related topics, such as cosmetics, skincare products, body care routines, and make-up tutorials to the YouTube platform. Since she has the ability to speak in English, Molita Lin significantly uses English terms while explaining something in her videos. Therefore, this study was aimed to provide an important opportunity to advance the understanding the types of code mixing as well as the reasons of the occurrences of code mixing in one of Molita Lin’s YouTube video entitled “SKINCARE UNTUK PEMULA ANTI RIBET | Day and Night” by using documentation method as the method of data collection. and then the data were analyzed descriptively and qualitatively by applying theories proposed by Hoffman regarding types and the reasons of code mixing. As an outcome, this study concluded that in the Molita Lin’s video transcribe, there are three types of code mixing and only four out of seven reasons of code mixing that can be observed.